Use of Qualitative Research Approach in Postmodern Studies: Sharing of Some Anthropological Experiences of the Study on the Pahari People of Central Nepal - Khadka, Anju (Nepalese Journal of Qualitative Research Methods, 2009)
doi: 10.3126/njqrm.v1i0.1971 Keywords: postmodern studies; Pahari People Nepalese Journal of Qualitative Research Methods Vol.1 2007 pp.37-50